Regional cerebral hypoperfusion as a cause of symptoms and progression of multiple sclerosis - L. N. Prakhova (Bûlleten' Sibirskoj Mediciny, 2020)
Background. Neurodegenerative processes play an important role in the development of clinical features of multiple sclerosis (MS) as well as in the progression of the disease. At the same time, neurodegenerative mechanisms of MS are not completely clear, which makes researchers pay special attention to pathogenetic aspects of the disease that have not been studied before. Previously it was shown that MS patients can have alterations in the local cerebral blood flow, however, the meaning of the detected abnormalities is still not clear.The aim of our work is to evaluate the perfusion character in the demyelinating lesions and normalappearing brain structures, and to determine their relation to clinical features of MS.Material and methods. 49 patients with relapsing-remitting and secondary progressive MS with clinical and MRI remission were included in the study. The patients underwent contrast-enhanced MR perfusion of the brain on the 3 Tesla MR-tomograph, as well as the Functional System Score, Expanded Disability Status Score and Fatigue Status Score evaluation. The data analysis included automatic construction of perfusion maps of the cerebral blood volume (CBV), cerebral blood flow (CBF) and mean transit time (MTT) values in the normal-appearing brain structures and in the demyelinating lesions and statistical analysis.Results. The received results allow to presume that variation of CBV values in MS lesions can indicate heterogeneity of processes in these lesions – from reactivation of inflammation to remyelination.Significant reduction of perfusion in nucleus lenticularis was revealed. This reduction did not depend on the severity of the disease and correlated negatively with the fatigue score. This allows to suppose that the therapy focused on brain perfusion improvement can be used as symptomatic therapy of MS. Considering the fact that regional hypoperfusion precedes the development of brain structure atrophy, it is hypothesized that the improvement of perfusion may prevent neurodegeneration in MS. The obtained findings need further investigation.